SIFAT SENSORIS ASAP CAIR TEMPURUNG KELAPA HASIL ADSORPSI PADA ZEOLIT - syahraeni kadir (Universitas Tadulako, 2015)
Liquid smoke has a strong and pungent distinctive aroma caused by some contributor compounds within the product including phenolic, carbonyl and acid. Adsorption using zeolites in this study aimed to reduce the levels of strong pungent aroma contributor compounds so that the liquid smoke can be accepted by consumers. Zeolite of various pH ie. 2, 3, 4, 5 and 6 were used as adsorbent liquid smoke. The fraction produced the adsorption was sensory analyzed by 20 panelists selected. The liquid smoke fraction selected based on the results of sensory testing was further analyzed using GC-MS. Data was analyzed using analysis of variance (ANOVA) with SPSS software version 16, followed by Duncan range test at 1% level. The results showed that of 25 fractions of coconut shell liquid smoke generated by the zeolite adsorption at pH range of 2 – 6, 14 fractions were qualified for sensory tested while the remaining fractions had strong and pungent aroma. The contributor substances with strong and punge aroma in the liquid smoke found include phenol groups, carbonyl and acid. The adsorption of coconut shell liquid smoke using zeolite effectively reduce strong pungent aroma of the product. It is necessary to evaluate the shelf life of the liquid smoke adsorbed by zeolite.